Raman and ESR study of gas detonation deposited hydroxyapatite coatings - Dzhagan, V.M.; Valakh, M.Ya.; Konchits, A.A.; Vorona, I.P.; Yefanov, V.S.; Klyui, M.I.; Temchenko, V.P.; Dubok, V.A. (Functional Materials, 2009)
Structural modification of hydroxyapatite (HAP) formed by gas detonation HAP deposition on metal substrates has been studied using Raman spectroscopy and electron spin resonance (ESR) techniques. It was revealed, that the detonation deposition of the initial HAP powder has been found to result in a considerable broadening of the main Raman band peaked at 960 cm⁻¹ and the appearance of additional ones near 947 cm⁻¹ and 970 cm⁻¹. In ESR spectra, the signals originated from intrinsic HAP defects such as O₃⁻-radicals and F-centers are observed. The changes in the Raman and ESR spectra indicate local variations of HAP structure, namely amorphization at the coating/substrate interface, partial dehydration and increased concentration of intrinsic defects. Nucleation of a new structural phase, oxyapatite, has been also observed.